The State, Minorities, and Dilemmas of Development in Contemporary China - McCarthy, Susan K. (Tufts Archival Research Center, 2005)
Volume 26, Issue 2. Summer/Fall While the Chinese governmentï¿½s human rights practices certainly deserve criticism, the contemporary Chinese leadership has demonstrated tolerance, and even active support, for the reestablishment and resurgence of many minority cultural practices and institutions.